Passive house design : planning and design of energy-efficient buildings - Gonzalo, Roberto; Vallentin, Rainer (Munchen : Redaktion Detail, Institut fur internationale Architektur-Dokumentation, 2014)
In the course of the last two decades, the passive house standard has evolved into a key benchmark for energy-efficient construction. Passive houses are being erected in almost all parts of the world and for all types of users. At the same time, many architects are unsure about the specifics: What do passive houses really deliver, and what errors need to be avoided during planning? This book provides architects with the confidence required to deal with the passive house standard. It shows where there is significant scope for design and explains design strategies that lead to better passive houses. A selection of international buildings illustrate how design, construction and building technology combine in passive houses. Chapters on building physics, building services engineering and energy balancing round out the planning guidelines.
Translation of'Passivhser entwerfen : Planung und Gestaltung hocheffizienter Gebde.'
'Translation: Sharon Heidenreich.'--Page 4.
'Edition DETAIL Green Books.'--Title page.
'A specialist book from Redaktion DETAIL.'--Page 4.
Includes bibliographical references and subject index.
Keywords: Architecture and energy conservation; Architecture -- Environmental aspects; Sustainable buildings -- Design and construction; Architecture, Domestic -- Environmental aspects; Ecological houses